Keanekaragaman Kupu-Kupu (Lepidoptera: Rhopalocera) di Kawasan Ekowisata Dusun Kaliurang Timur, Yogyakarta - Fasa, ‘Uliya Ma’rifati Arifina; Aisah, Siti (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2023)
Butterflies act as bioindicators and pollinators of the environment. Ecotourism development poses a threat to butterfly life due to high human activity and land degradation. This study aims to determine the diversity of butterflies (Rhopalocera), diversity index, evenness index, dominance index, similarity index, and abiotic parameters at each sampling location. The data was collected at Tlogo Putri, settlements, and Tankaman Natural Park, whose location selection was based on purposive sampling and using the point count method. Based on the research obtained 55 species with a total of 294 individuals, diversity index (TP: 2.88; P: 2.51; TNP: 2.66), evenness index (TP: 0.86; P: 0.75; TNP: 0.84), dominance index (TP: 0.08; P: 0.14; TNP: 0.09), species similarity index (TP & P: 46.42; TP & TNP: 27.45). Abiotic parameters in the ecotourism area of Kaliurang Timur Hamlet are altitude of 814-889 meters above sea level, temperature of 26-28°C, air humidity of 10-45%, light intensity of 7571-4877x10 lux, wind speed of 0-1 m/s, and rainfall of 0-20. The conclusion of this study is that 55 species of Rhopalocera order were found, the diversity index is moderate, the evenness index is high, the dominance index and the similarity index are low at each sampling location. Abiotic parameters measured were in the normal range for Rhopalocera life in the ecotourism area of Kaliurang Timur Hamlet.